(untitled) - Cespedes, Frank V. (Boston, Massachusetts, 2014)
In Aligning Strategy and Sales, Harvard Business School professor Frank Cespedes equips you to link your go-to-market initiatives with strategic goals. Cespedes offers a road map to articulate strategy in ways that people in the field can understand and that will fuel the behaviors required for profitable growth. Without that alignment, leaders will press for better execution when they need a better strategy, or change strategic direction with great cost and turmoil when they should focus on the basics of sales execution.
Keywords: Quản lý bán hàng,Sales management